2006
DOI: 10.1097/01.mpg.0000189338.15763.4a
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in Brazilian Children with Type 1 Diabetes Mellitus

Abstract: Measurement of antigliadin antibodies in patients with diabetes mellitus type 1 helped in the selection of patients to undergo jejunal biopsy. Antiendomysial antibodies were highly specific and moderately sensitive in predicting celiac disease. The prevalence of celiac disease was higher in diabetics than in the general population, suggesting the need for regular screening assessment of diabetic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
2
20
0
8
Order By: Relevance
“…Em 2006, Tanure e cols. (6) realizaram um estudo sobre a prevalência da DC em crianças e adolescentes com DM1 e acompanhamento no Serviço de Endocrinologia Pediátrica do Hospital das Clínicas da Universidade Federal de Minas Gerais, Belo Horizonte, sendo encontrada prevalência de 2,6%.…”
Section: Prevalência Da Doença Celíaca No Dm1unclassified
“…Em 2006, Tanure e cols. (6) realizaram um estudo sobre a prevalência da DC em crianças e adolescentes com DM1 e acompanhamento no Serviço de Endocrinologia Pediátrica do Hospital das Clínicas da Universidade Federal de Minas Gerais, Belo Horizonte, sendo encontrada prevalência de 2,6%.…”
Section: Prevalência Da Doença Celíaca No Dm1unclassified
“…Approximately 4% of patients with IDDM have concomitant CD (30,59) . In Brazil, TANURE et al (64) reported a prevalence of 2.6 % among 234 children and adolescents with IDDM using IgA and IgG antigliadin antibodies (AGA) followed by IgA EmA.…”
Section: Endocrinological Disordersmentioning
confidence: 99%
“…In our study performed using anti-tTG IgA antibodies, we detected serologic positivity in 16 (7.3%) out of 218 cases. In another study, Tanure et al [22] detected serologic positivity in 21 (21/234; 8.9%), CD in 10 (10/234; 2.4%), and latent CD in nine (9/234; 3.9%) of cases with type 1 DM, respectively. In some studies, the incidence of CH confirmed by biopsy has varied from 2.4% to 12.1% [21,23].…”
Section: Discussionmentioning
confidence: 99%